The ST. FRANSISKUS XAVERIUS: MISIONARIS, TELADAN IMAN DAN GURU BAGI MASYARAKAT KATOLIK - Adison Adrianus Sihombing; Masmedia Pinem (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
Every society has a role model, because folklore is always related to a particular society. This study aims to elaborate and actualize the religious values ​​that have been exemplified by St. Fransiskus Xavier in Maluku religious folklore. This study is based on qualitative research with a descriptive approach. Data collection techniques through observation, interviews, and documentation studies. The process of data analysis was carried out with data collection, data display, data reduction, and conclusion drawing. The results showed that the example of faith and personal qualities of St. Francis Xavier as a missionary who laid the foundations of Christianity in Maluku was very meaningful for the people of Maluku because it had changed their lives to know and believe in God. Therefore, this story is passed down from generation to generation so that it continues to be present in the public's memory. This folklore teaches the noble values ​​that have been exemplified by Francis, namely being religious, generous, simple, hardworking and faithful in faith. His life example gives a message that people who live close to God will be a blessing to others. Keywords: Religion, Fransiskus Xaverius, Missionary, Maluku. Setiap masyarakat memiliki panutan/tokoh, karena cerita rakyat selalu berkaitan tentang masyarakat tertentu. Studi ini bertujuan mengelaborasi dan mengaktualisasikan nilai-nilai religius yang telah diteladankan oleh St. Fransiskus Xaverius dalam folklor religi Maluku. Studi ini didasarkan pada penelitian kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Proses analisis data dilakukan dengan data collection, data display, data reduction, dan conclusion drawing. Hasil penelitian menunjukkan bahwa teladan iman dan kualitas pribadi St. Fransiskus Xaverius sebagai seorang misionaris peletak dasar kekristenan di Maluku sangat bermakna bagi masyarakat Maluku karena telah mengubah hidup mereka menjadi mengenal dan beriman kepada Allah. Oleh karena itu cerita ini diwariskan secara turun temurun sehingga terus hadir dalam ingatan publik. Folklor ini mengajarkan nilai-nilai luhur yang telah diteladankan oleh Fransiskus, yakni religius, murah hati, sederhana, kerja keras dan setia dalam iman. Teladan hidupnya memberi pesan bahwa orang yang hidup dekat dengan Tuhan, akan menjadi berkat bagi orang lain. Kata kunci: Religi, Fransiskus Xaverius, Misionaris, Maluku.